An Introduction to Western Nigeria : its people, culture, and system of government - Adedeji, Adebayo ([Ife] Nigeria : Institute of Administration, University of Ife, 1967)
The volume contains six papers presented at an orientation seminar held for some officials of the Federal Public Service of Nigeria in September, 1996, at the institute of Administration, University of Ife. The seminar was meant to introduce participants to Western Nigeria, Its people, culture and system of government so as to give them some understanding of the social, cultural, political and economic development and problems of the region.
Includes bibliographical footnotes.
aia 07/04/2017
Loans
Keywords: Politics and government; Nigeria, Western; Western State